High throughput screening of human subtelomeric DNA for copy number changes using multiplex amplifiable probe hybridisation (MAPH). Issue 11 (1st November 2002) - Hollox, E J; Atia, T; Cross, G; Parkin, T; Armour, J A L
Abstract : Background: Subtelomeric regions of the human genome are gene rich, with a high level of sequence polymorphism. A number of clinical conditions, including learning disability, have been attributed to subtelomeric deletions or duplications, but screening for deletion in these regions using conventional cytogenetic methods and fluorescence in situ hybridisation (FISH) is laborious. Here we report that a new method, multiplex amplifiable probe hybridisation (MAPH), can be used to screen for copy number at subtelomeric regions. Methods: We have constructed a set of MAPH probes with each subtelomeric region represented at least once, so that one gel lane can assay copy number at all chromosome ends in one person. Each probe has been sequenced and, where possible, its position relative to the telomere determined by comparison with mapped clones. Results: The sensitivity of the probes has been characterised on a series of cytogenetically verified positive controls and 83 normal controls were used to assess the frequency of polymorphic copy number with no apparent phenotypic effect. We have also used MAPH to test a cohort of 37 people selected from males referred for fragile X syndrome testing and found six changes that were confirmed by dosage PCR. Conclusions: MAPH can be used to screen subtelomeric regions of chromosomes for deletions and duplications before confirmation by FISH or dosage PCR. The high throughput nature of this technique allows it to be used for large scale screening of subtelomeric copy number, before confirmation by FISH. In practice, the availability of a rapid and efficient screen may allow subtelomeric analysis to be applied to a wider selection of patients than is currently possible using FISH alone.